Using HEK293T Expression System to Study Photoactive Plant Cryptochromes - Yang, Liang; Wang, Xu; Deng, Weixian; Mo, Weiliang; Gao, Jie; Liu, Qing; Zhang, Chuanyu; Wang, Qin; Lin, Chentao; Zuo, Zecheng (Frontiers in Plant Science, 2016)
Cryptochromes are photolyase-like blue light receptors that are conserved in plants and animals. Although the light-dependent catalytic mechanism of photolyase is well studied, the photochemical mechanism of cryptochromes remains largely unknown. Lack of an appropriate protein expression system to obtain photochemically active cryptochrome holoproteins is a technical obstacle for the study of plant cryptochromes. We report here an easy-to-use method to express and study Arabidopsis cryptochrome in HEK293T cells. Our results indicate that Arabidopsis cryptochromes expressed in HEK293T are photochemically active. We envision a broad use of this method in the functional investigation of plant proteins, especially in the large-scale analyses of photochemical activities of cryptochromes such as blue light-dependent protein-protein interactions.